ANALYSIS OF PRODUCT QUALITY AND SERVICE QUALITY ON INTENTION TO REVISIT THROUGH CONSUMER SATISFACTION AS AN INTERVENING VARIABLE IN OWN PICKED ORANGE AGROTOURISM IN KARO DISTRICT - Indra Wahyudi; Elisabet Siahaan; Rahmanta (CV. Radja Publika, 2024)
The quality of self-picked orange agrotourism products does not yet have good quality in terms of the texture of the orange fruit, the size of the orange fruit is not uniform, and the taste of the orange fruit. Apart from that, the quality of service provided is not fully optimal, the agrotourism environment is not clean, the employees who work do not have special uniform attributes, the limited number of employees in agrotourism, so this will have an impact on the level of satisfaction consumers, if consumers who visit the self-picked orange agrotourism are satisfied with the product quality and service quality of the self-picked orange agrotourism, of course consumers/visitors will have an interest in visiting the self-picked orange agrotourism again. The analysis method used is path analysis using Smart PLS software version 3.0. The data used in this research are primary and secondary data. The sample in this research was 90 visitors or consumers of self-picking orange agrotourism. The research results show that the variables product quality (X1) and service quality (X2) have a positive and significant effect on consumer satisfaction (Z). The variables product quality (X1) and service quality (X2) have a positive and significant effect on intention to revisit (Y). The consumer satisfaction variable (Z) has a positive and significant effect on intention to revisit (Y). The product quality variable (X1) has a positive and significant effect on intention to revisit (Y) through consumer satisfaction (Z). The service quality variable (X2) has a positive and significant effect on intention to revisit (Y) through consumer satisfaction (Z).